Method for preparing high-energy-density lithium ion battery
Through the combination of negative electrode pre -lithiumization and positive excessive lithium, the problem of the NCM622 positive electrode material with the fragile structure and crystal structure, which significantly enhances the storage capacity of reversible lithium ions and the energy density of the battery.
Patent Information
- Application Number
- CN202411540794.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-10-31
AI Technical Summary
The energy band structure of the NCM622 positive electrode material limits the expansion space of voltage, and the crystal structure is fragile, making it difficult to withstand the stress changes of the deep embedding/exit of lithium ions, resulting in limited increase in its actual available capacity.
By combining the pre-lithiation of the negative electrode and the over-lithiation of the positive electrode, the pre-lithiation process and the degree of over-lithiation of the positive electrode are finely controlled to increase the reversible lithium ion storage capacity of the NCM622 material.
It significantly increases the content of lithium ions in NCM622 materials, enhances the energy density of cylindrical lithium ion batteries, while maintaining the structural stability of the material, delaying the decline of the battery capacity.
Smart Images

Figure CN119340496A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of lithium ion batteries, in particular to a method for preparing a high energy density lithium ion battery. Background Art
[0002] Layered transition metal oxide cathode materials, as the leaders in the core components of lithium-ion batteries, have opened up a new path for building high-capacity and high-energy-density lithium-ion batteries with their unique intercalation chemistry mechanism. Among these materials, NCM622 (lithium nickel cobalt manganese oxide with a nickel-cobalt-manganese ratio of 6:2:2) occupies an important position in the commercial lithium-ion battery market with its excellent reversible capacity performance, outstanding chemical stability and cost control advantages. However, despite the many advantages of NCM622, its inherent physical and chemical properties also constitute an obstacle to further development: its band structure limits the expansion space of its upper voltage limit, and the fragility of the crystal structure cannot withstand the stress changes caused by the deep insertion / extraction of lithium ions. These factors jointly restrict the further improvement of its actual available capacity, thus becoming a key bottleneck for the breakthrough of high-energy-density lithium-ion battery technology.
[0003] In order to significantly improve the energy density of NCM622 ternary materials, the method currently widely used in the industry is to increase the nickel (Ni) content in the positive electrode material or increase its charging cut-off voltage. However, this strategy has significant disadvantages: excessive increase in Ni content will weaken the structural stability of the material, accelerate its transformation from ordered layered to disordered spinel and even rock salt structure, and thus lead to a surge in interface impedance and a sharp drop in reversible capacity. In addition, excessive Ni content or increased charging cut-off voltage may also induce lattice collapse, a surge in internal mechanical stress, frequent particle breakage, and intensified side reactions, ultimately significantly accelerating the decline of battery capacity. Summary of the invention
[0004] The present invention provides a method for preparing a high energy density lithium ion battery, and creatively proposes a solution combining negative electrode pre-lithiation with positive electrode over-lithiation.
[0005] A method for preparing a high energy density lithium ion battery comprises the following steps: Step 1: Pre-lithiation treatment of negative electrode sheet: Stable lithium metal powder, styrene-butadiene rubber and toluene are mixed and dispersed evenly in proportion to prepare a pre-lithiation reagent. The pre-lithiation reagent is sprayed evenly onto the surface of the graphite electrode sheet. After the toluene solvent on the surface of the electrode sheet is completely evaporated, the electrode sheet is rolled at a low speed to complete the pre-lithiation treatment of the graphite electrode sheet. Step 2: Negative electrode pre-lithiation process: Assemble the treated graphite electrode sheet and NCM622 electrode sheet into a cylindrical battery, and complete the liquid injection, high temperature immersion and standing to complete the negative electrode pre-lithiation; Step 3: Positive electrode overlithiation process: discharge the battery at a constant current density of 0.01C to 0.5V; Step 4: Battery formation: 1) Charge the battery to 4.2V at a constant current density of 0.05C; 2) Allow to stand for 30 minutes; 3) Charge the battery to 4.2V at a constant current density of 0.1C; 4) Allow to stand for 15 minutes; 5) Charge the battery to 4.2V at a constant current density of 0.2C; 6) Allow to stand for 10 minutes; Step 5: Perform high temperature aging and secondary liquid filling operations on the battery in sequence; Step 6: Capacity division: 1) Charge the battery to 4.2V at a constant current of 0.5C; 2) Charge at a constant voltage of 4.2V until the current drops to 0.05C; 3) Let stand for 30 minutes; 4) Discharge the battery to 3.0V at a constant current of 0.5C; 5) Charge the battery to 3.0V at a constant current of 0.2C; 6) Charge the battery to 3.0V at a constant current of 0.1C; 7) Let stand for 30 minutes; 8) Charge the battery to 30 minutes at a constant current of 0.5C; 9) Let stand for 30 minutes.
[0006] Preferably, in step 1, the pre-lithiation reagent is 3 g of stable lithium metal powder dissolved in 1 L of toluene-styrene-butadiene rubber mixed solution, wherein the ratio of toluene to styrene-butadiene rubber in the toluene-styrene-butadiene rubber mixed solution is 9:1.
[0007] Preferably, the speed of the low-speed rolling in step 1 is 0.1 m / min.
[0008] Preferably, the pressure of the low-speed rolling in step 1 is 10 Mpa.
[0009] Preferably, the temperature of the high-temperature soaking and standing in step 2 is 45° C. and the time is 24 hours.
[0010] Preferably, the high temperature aging temperature in step 5 is 45°C.
[0011] Compared with the existing technology, the present invention focuses on the over-lithiation technology of NCM622 ternary materials. By finely controlling the pre-lithiation process and the degree of over-lithiation of the positive electrode, the storage capacity of reversible lithium ions in NCM622 materials is effectively increased, opening up a new path for the development of high-energy-density batteries. More importantly, this technological innovation achieves a significant increase in the reversible lithium-ion content in NCM622 materials without affecting the existing production process framework of cylindrical batteries, thereby directly enhancing the energy density of cylindrical batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 Schematic diagram of step 1.
[0013] Figure 2 This is a schematic diagram of step 4.
[0014] Figure 3 This is a schematic diagram of step 6.
[0015] Figure 4 This is the voltage-time curve of the NCM622 over-lithiation process.
[0016] Figure 5 Comparison of XRD patterns of original and over-lithiated NCM622.
[0017] Figure numerals: 1. pre-lithiation reagent tank; 2. graphite coating; 3. copper foil; 4. pre-lithiation reagent layer; 5. oven; 6. roller press. DETAILED DESCRIPTION
[0018] In the description of the present invention, it should be understood that the terms "center", "longitudinal", "lateral", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first", "second", and the like are only used for descriptive purposes, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, features defined as "first", "second", and the like may explicitly or implicitly include one or more of the features.
[0019] In the description of the present invention, unless otherwise specified, "plurality" means two or more.
[0020] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood by specific circumstances.
[0021] like Figure 1-3 A method for preparing a high energy density lithium ion battery is shown, comprising the following steps: 1. Negative electrode pre-lithiation pre-treatment process: Stable lithium metal powder, styrene butadiene rubber and toluene are mixed and dispersed in proportion to prepare pre-lithiation reagent, the ratio is 3g stable lithium metal powder dissolved in 1L toluene-styrene butadiene rubber mixed solution, the toluene:styrene butadiene rubber ratio in the toluene-styrene butadiene rubber mixed solution is 9:1. The pre-lithiation reagent is evenly sprayed onto the surface of the graphite electrode sheet. After the toluene solvent on the surface of the electrode sheet is completely evaporated, the electrode sheet is rolled at a low speed (0.1m / min) with a pressure of 10 Mpa to complete the pre-lithiation pre-treatment of the graphite electrode sheet.
[0022] The electrode sheet is mainly composed of a current collector and a graphite coating. Copper foil is the current collector. Graphite is coated on the copper foil and dried to form a graphite coating. Then, a pre-lithiation reagent is sprayed on the surface of the graphite coating. After the solvent evaporates, the production process of the graphite electrode sheet is completed. The subsequent operations are winding the battery cell, injecting liquid, etc.
[0023] 2. Negative electrode pre-lithiation process: Assemble the treated graphite electrode sheet and NCM622 electrode sheet into a cylindrical battery, and complete the liquid injection, high temperature (45°C) immersion and standing for 24 hours to complete the negative electrode pre-lithiation. Negative electrode pre-lithiation process: During the high-temperature standing process, the electrons in the lithium metal powder migrate to the graphite due to the potential difference, and the generated lithium ions are dissolved in the electrolyte on the surface of the negative electrode. In order to maintain electrical neutrality, lithium ions will spontaneously migrate into the graphite and combine with electrons to achieve the pre-lithiation effect; 3. Positive electrode over-lithiation process: The battery is discharged at a constant current density of 0.01C to 0.5V to activate the high energy density characteristics of NCM622 material; 4. Battery formation: 1) Charge the battery to 4.2V at a constant current density of 0.05C; 2) Let it stand for 30 minutes; 3) Charge the battery to 4.2V at a constant current density of 0.1C; 4) Let it stand for 15 minutes; 5) Charge the battery to 4.2V at a constant current density of 0.2C; 6) Let it stand for 10 minutes.
[0024] 5. Perform high temperature (45°C) aging and secondary liquid filling operations on the battery in sequence; 6. Capacity division: 1) Charge the battery to 4.2V at a constant current density of 0.5C; 2) Charge at a constant voltage of 4.2V until the current drops to 0.05C; 3) Let stand for 30 minutes; 4) Discharge the battery to 3.0V at a constant current density of 0.5C; 5) Charge the battery to 3.0V at a constant current density of 0.2C; 6) Charge the battery to 3.0V at a constant current density of 0.1C; 7) Let stand for 30 minutes; 8) Charge the battery to 30 minutes at a constant current density of 0.5C; 8) Let stand for 30 minutes.
[0025] In the prior art, after the battery is manufactured, the formation operation should be performed, that is, charging should be performed first, and the voltage should increase over time. However, the positive electrode over-lithiation strategy in the present invention is to discharge the battery first, that is, the voltage gradually decreases over time (this process is to embed more / excessive lithium ions into the material). After this process, the structure of the NCM622 material will change, that is, the NCM622 material can accommodate more lithium ions for reversible embedding and extraction in the subsequent cycle process. Figure 4 As shown in the figure, the voltage platform near 1.7V corresponds to the first stage of excessive lithium ion embedding in NCM622 material. The embedded lithium ions in this stage are irreversibly de-embedded, and the crystal structure of NCM622 material is still 1T phase in this stage; then in the range of 1.7V-0.8V, with the further embedding of more lithium ions, the structure of NCM622 material begins to change from 1T phase to O3 phase (this process is a solid solution reaction, that is, the crystal structure of the material begins to change from 1T phase to O3 phase, 1T phase means that excessive embedded lithium ions cannot be reversibly de-embedded, and O3 phase means that embedded lithium ions can be reversibly de-embedded. Then, in the range of 0.8V-0.5V, accompanied by the embedding of excess lithium ions and the phase change of the material (the 1T phase is further transformed into the O3 phase), more excess lithium ions can be embedded in this stage, and the structure is further transformed into the O3 phase. That is, after completing this stage, the NCM622 material not only stores lithium ions far exceeding the original stoichiometric ratio, but also changes in the material structure to convert this part of the excess lithium ions into active lithium ions that can be reversibly deintercalated. Therefore, even in the subsequent long cycle, the NCM622 material can still store more lithium ions for reversible deintercalation, which ultimately greatly increases the energy density of the lithium-ion battery.
[0026] Under normal temperature conditions, two groups of cylindrical batteries were used for a systematic comparative experiment. The other group was manufactured according to the method used in the present invention, and steps 1-3 were not used in the production process of one group of batteries. Figure 5 As shown in the figure, the (003) crystal plane strength of the over-lithiation NCM622 material is about twice that of the original NCM622, which means that the number of active lithium ions stored in the NCM622 material has increased, which ultimately greatly increases the energy density of the lithium-ion battery.
[0027] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.
Claims
1. A method for preparing a high energy density lithium ion battery, characterized in that: The following steps are involved: Step 1: Pre-lithiation treatment process of negative electrode sheet: Stable lithium metal powder, styrene-butadiene rubber and toluene are mixed and dispersed evenly in proportion to prepare a pre-lithiation reagent, and the pre-lithiation reagent is evenly sprayed onto the surface of the graphite electrode sheet. After the toluene solvent on the surface of the electrode sheet is completely evaporated, the electrode sheet is rolled at a low speed to complete the pre-lithiation treatment of the graphite electrode sheet; Step 2: Negative electrode pre-lithiation process: Assemble the treated graphite electrode sheet and NCM622 electrode sheet into a cylindrical battery, and complete the liquid injection, high temperature immersion and standing to complete the negative electrode pre-lithiation; Step 3: Positive electrode overlithiation process: discharge the battery at a constant current density of 0.01C to 0.5V; Step 4: Battery formation: 1) Charge the battery to 4.2V at a constant current density of 0.05C; 2) Allow to stand for 30 minutes; 3) Charge the battery to 4.2V at a constant current density of 0.1C; 4) Allow to stand for 15 minutes; 5) Charge the battery to 4.2V at a constant current density of 0.2C; 6) Allow to stand for 10 minutes; Step 5: Perform high temperature aging and secondary liquid filling operations on the battery in sequence; Step 6: Capacity division: 1) Charge the battery to 4.2V at a constant current of 0.5C; 2) Charge at a constant voltage of 4.2V until the current drops to 0.05C; 3) Let stand for 30 minutes; 4) Discharge the battery to 3.0V at a constant current of 0.5C; 5) Charge the battery to 3.0V at a constant current of 0.2C; 6) Charge the battery to 3.0V at a constant current of 0.1C; 7) Let stand for 30 minutes; 8) Charge the battery to 30 minutes at a constant current of 0.5C; 9) Let stand for 30 minutes.
2. The method for preparing a high energy density lithium ion battery according to claim 1, characterized in that: In step 1, the pre-lithiation reagent is 3 g of stable lithium metal powder dissolved in 1 L of toluene-styrene-butadiene rubber mixed solution, wherein the ratio of toluene to styrene-butadiene rubber in the toluene-styrene-butadiene rubber mixed solution is 9:
1.
3. The method for preparing a high energy density lithium ion battery according to claim 1, characterized in that: The speed of the low-speed rolling in step 1 is 0.1 m / min.
4. The method for preparing a high energy density lithium ion battery according to claim 1, characterized in that: The pressure of the low-speed rolling in step 1 is 10 Mpa.
5. The method for preparing a high energy density lithium ion battery according to claim 1, characterized in that: In step 2, the temperature of high temperature soaking is 45°C and the time is 24h.
6. The method for preparing a high energy density lithium ion battery according to claim 1, characterized in that: The temperature of high temperature aging in step 5 is 45°C.
Citation Information
Patent Citations
Lithium-supplementing negative pole piece and preparation method thereof and lithium ion battery
CN112599723A
Pre-lithiation method and application of lithium ion battery
CN116722239A
Lithium supplement negative electrode, preparation method thereof and lithium battery
CN118156425A
Composite silicon negative pole piece and preparation method thereof, lithium ion battery and electric equipment
CN118299518A
Anode for lithium secondary battery, manufacturing method therefor, and lithium secondary battery comprising anode for lithium secondary battery
WO2019164319A1